E-Communication between Citizens and Local Government - Pavlova, Yoana (Research Papers, 2018)
This report looks at the concept of "citizenship" in the context of local government. Different practices of communication and interaction between citizens and local administration are analyzed. An attempt has been made to identify good and working practices and to outline problem areas with possible solutions.
Keywords: Communication; Citizens; Administration; Management